Clinical impact of tetracyclines and/or proton pump inhibitors on the efficacy of epidermal growth factor receptor inhibitors in non-small cell lung cancer: a retrospective cohort study - Hsieh, Hui-Hsia; Wu, Tien-Yuan; Chen, Chi-Hua; Kuo, Yu-Hung; Hour, Mann-Jen (BMC cancer, 2023)
This retrospective cohort study examined the impact of tetracyclines (TCs) and proton pump inhibitors (PPIs) alone or in combination on the efficacy of epidermal growth factor receptor tyrosine kinase inhibitors (EGFR-TKIs) in patients with non-small cell lung cancer (NSCLC). Patients with NSCLC treated with gefitinib or erlotinib for at least 1 week between January 2009 and October 2021 were enrolled and divided into four groups based on the presence/absence of TC and/or PPI in the therapeutic regimen: TC-/PPI-, TC + /PPI-, TC-/PPI + , TC + /PPI + . Progression-free survival (PFS) and overall survival (OS) were the primary and secondary endpoints, respectively. The estimated median PFS and OS of 347 included patients with NSCLC were 8.57 (95% confidence interval [CI]: 7.66-9.48) months and 13.10 (95% CI: 11.03-15.17) months, respectively. Co-administration of EGFR-TKIs with PPIs decreased the PFS and OS, while that with TCs improved the PFS and OS. However, the concomitant use of EGFR-TKIs, TCs, and PPIs yielded survival rates similar to that of EGFR-TKI therapy alone. The administration of EGFR-TKIs with other drugs poses a challenge in managing patients with NSCLC. Therefore, reassessing the indications and necessity of TC or PPI therapy is essential for patients receiving erlotinib or gefitinib. The benefits and risks of possible discontinuation due to the clinical relevance of this interaction should be considered.